Anomalous Posterior Tibial Artery Course—Anatomic Considerations for the Posterolateral Ankle Approach: A Case Report. Issue 1 (3rd January 2023) - Perugini, Anthony J.; Passias, Braden J.; Pelz, Nicholas C.; Temperato, Joseph R.; Mehta, Sanjay
Abstract : Case: We report a unique anatomical case of an anomalous course of the posterior tibial artery found on dissection during the posterolateral approach to the ankle. To the best of our knowledge, no such case has been documented. Conclusion: The vascular bundle consistent with that of the posterior tibial artery and vein was encountered in the far lateral aspect of the deep posterior compartment, which suggests physicians should proceed with caution when performing the posterolateral approach to the ankle so as to avoid iatrogenic injury of this named anatomic structure.